Effectiveness of an Educational Program on Parents’ Knowledge about Home Health Care Management to Children with Beta Thalassemia-Major at Thalassemia Center in Al-Zahra Teaching Hospital for Maternity and Children in Al-Najaf City - Riyadh Saad Atshan, Afifa Radha Aziz (Pakistan Journal of Medical & Health Sciences, 2022)
Background Thalassemia is a hereditary condition that affects the formation of globin chains. Children with βeta-thalassemia major have a complete absence of globin production. βeta thalassemia- major is a severe type of disease that require life-long blood transfusions for survival. Objectives: To evaluate the effectiveness of an educational program on parents’ knowledge regarding home health care management related to children with Beta Thalassemia-Major Methodology: A quasi experimental study was carried out at Thalassemia Center in Al-Najaf City during the periods 25 February 2021 to 20 March 2022. Non-probability (purposive) sample of (70) parents were selected from thalassemia center (38 mothers and 32 fathers). Results: The study findings show that there are high significant difference in overall main domains relating parents’ knowledge of beta-thalassemia major between pre and post-tests 1&2 in the study group. In addition there is a statistical relationship between parental knowledge with regard to their age. Also there is high statistical significant relationship during parents’ knowledge with regard to their educational level Conclusion: The study finds that the efficacy of an educational program to improving parents’ knowledge of home health care management for children with β-Thalassemia Major is high